Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3174/ajnr.a4228
|View full text |Cite
|
Sign up to set email alerts
|

Comparing 3T and 1.5T MRI for Mapping Hippocampal Atrophy in the Alzheimer's Disease Neuroimaging Initiative

Abstract: BACKGROUND AND PURPOSE Prior MR imaging studies, primarily at 1.5T, established hippocampal atrophy as a biomarker for Alzheimer disease. 3T MR imaging offers a higher contrast and signal-to-noise ratio, yet distortions and intensity uniformity are harder to control. We applied our automated hippocampal segmentation technique to 1.5T and 3T MR imaging data, to determine whether hippocampal atrophy detection was enhanced at 3T. MATERIALS AND METHODS We analyzed baseline MR imaging data from 166 subjects from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 64 publications
5
51
1
2
Order By: Relevance
“…In a previous study, Jovicich and colleagues computed brain structure volumes from various scan protocols at both 1.5T and 3T and showed that field strength may bias the measurement of gray matter areas. In addition, Chow and colleagues showed a superior signal‐to‐noise ratio and a greater effect size in detecting hippocampal atrophy in patients with Alzheimer's disease or mild cognitive impairment as compared to NC at 3T versus 1.5T. Examination of our segmentation maps indicated that the 1.5T images produced lower tissue contrast.…”
Section: Discussionmentioning
confidence: 75%
“…In a previous study, Jovicich and colleagues computed brain structure volumes from various scan protocols at both 1.5T and 3T and showed that field strength may bias the measurement of gray matter areas. In addition, Chow and colleagues showed a superior signal‐to‐noise ratio and a greater effect size in detecting hippocampal atrophy in patients with Alzheimer's disease or mild cognitive impairment as compared to NC at 3T versus 1.5T. Examination of our segmentation maps indicated that the 1.5T images produced lower tissue contrast.…”
Section: Discussionmentioning
confidence: 75%
“…Most of the previously published longitudinal studies (Table 1) were conducted at 1.5T [7, 8, 1014]. The superior signal to noise ratio associated with 3T [47, 48] is critical for delineating hippocampal subfields [49]. …”
Section: Discussionmentioning
confidence: 99%
“…Postmortem studies suggest early involvement of ERC, subiculum, CA1 and dentate gyrus in AD,41 and hippocampal atrophy is well established as a biomarker for AD 42. It is possible to delineate the subfields of the hippocampus using 3T MRI in vivo; at 1.5T and 3T CA1, CA2 and subiculum atrophy (using both field strengths to image the same participants) was found in AD but not in MCI 17. In this paper, improved SNR and greater effect sizes were noted at 3T (compared with 1.5T), suggesting that a similar further improvement might be seen with an increase of B 0 to 7T.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging dementia research is largely concerned with the discovery of new biomarkers with such aims as earlier diagnosis, identification of ‘at-risk’ individuals and those with ‘prodromal’ dementia syndromes, monitoring of disease progression and identification of new treatment targets by illuminating the natural history of the disease in vivo. Increasing static field strength (B 0 ) from 1.5T to 3T has allowed imaging of macro and microstructures in the brain, for example, analysis of whole hippocampal volumes and differentiation between hippocampal subfield volumes in health and disease 17. However, even at 3T, MRI voxels typically measure millimetres.…”
Section: Introductionmentioning
confidence: 99%